Power and restraint in China's rise - Huang, Chin-Hao (New York, USA: Columbia University Press, 2022)
"The conventional wisdom holds that China's rise is disrupting the global balance of military and economic power in unpredictable ways. In this book, Chin-Hao Huang examines a phenomenon in China's rise to power that often gets overlooked: why and how does China exercise restraint? Huang reasons that a rising power's aspirations for acceptance-or legitimacy-by other states provide a key rationale for restraint. Power that draws on validation is more enduring than power that rests on pure military clout and coercion. Put simply, conformity with accepted international security norms expands one's overall influence. Legitimacy induces restraint, rather than conflict and aggression, in foreign policy behavior. The book identifies two conditions for China's restraint: the degree of diversification in its foreign policy decision-making process away from the military, and the level of international consensus on an emerging security norm. These conditions are evaluated with three empirical case studies: China's behavior in UN peacekeeping operations, the Arms Trade Treaty negotiations regulating global trade in conventional arms, and the ongoing maritime disputes in the South China Sea. The findings provide insights into understanding change in contemporary Chinese foreign policy, especially what has worked in the recent past, what has not, and what is likely to work in the future in incentivizing China to assume the role of a responsible power"--
Includes bibliographical references and index.
Keywords: Security, International -- Government policy -- China; China - History; Foreign Relation; Security; Civil-military relations -- China; China -- Foreign relations -- 21st century; China -- Foreign relations -- Decision making; China -- Military policy